Sikap Kerja, Masa Kerja, dan Usia terhadap Keluhan Low back pain pada Pengrajin Batik - Saputra, Andi (Jurusan Ilmu Kesehatan Masyarakat, Fakultas Ilmu Keolahragaan, Universitas Negeri Semarang, Indonesia, 2020)
LBP is major cause of activity limitation and work absenteeism, in most parts of the world, such as in the UK with more than 100 million work days lost every year. LBP is the second highest disease in Indonesia, reaching 7.6% -37%. The purpose of this study was to determine work attitudes, years of service, working age against LBP complaints on batik craftsmens. This type of research is quantitative analytic with cross sectional case design. Using purposive sampling technique. The results showed a significant relationship between work attitude and LBP complaints, with CI value of 9.41% and significance of 0.009 and a=0.05. There is significant relationship between work period with LBP complaints, with p=0.006 and PC=7.575. There was no relationship between age and LBP, with p=0.476 and PC=0.508. The conclusion of the study is that there is a relationship between work attitudes and work tenure with LBP complaints, and there is no relationship between age and LBP incidents in batik artisans in Batik Semarang 16. Keywords: LBP, work attitude, years of service, age, batik craftsmens